Temporal trends in classical and alternative flame retardants in bird eggs from Doñana Natural Space and surrounding areas (south-western Spain) between 1999 and 2013. (November 2015) - Barón, E.; Bosch, C.; Máñez, M.; Andreu, A.; Sergio, F.; Hiraldo, F.; Eljarrat, E.; Barceló, D.
Graphical abstract: Highlights: HFRs detected in bird eggs corresponding to two different time periods. Decrease of the contribution of the components of Penta-BDE in birds from South Spain. Ratio between HNs and PBDEs in each sample was higher in contemporary samples. Presence of PBDEs is still higher than the presence of HNs. Percentage contribution of α-HBCD increased between the two time periods. Abstract: Several halogenated flame retardants were detected in black kite, white stork and greater flamingo unborn eggs from Doñana Natural Space (Spain) collected in 1999, 2003, 2011 and 2013. The main components of Penta-BDE commercial mixture (BDE-47, -99 and -100) showed a decrease in the studied time interval, concurring with the ban of this mixture in the European Union (EU) in 2006. On the other hand, BDE-209, the main component of Deca-BDE mixture showed a clear trend in black kites but further monitoring is needed since its production ceased at the end of 2013. Besides, even if Dechlorane Plus (DP) was proposed by the EU as an alternative to BDE-209 no time trends were observed. Furthermore, total concentrations of PBDEs (classical FRs) are still higher than concentrations of hexabromocyclododecane (HBCD) and alternative FRs halogenated norbornenes (HNs), which are theoretically substitutes of the already banned PBDEs.